The impossible peace. Saint Augustine as antecedent to Political Realism (2008)
The papers main purpose is to expose the struggle between peace and war concepts in St. Augustine political work. The purpose will be to revise the psychological basements of St. Augustine Political Thought. Second, to expose the political consequences of